2009
DOI: 10.37358/rc.08.12.2053
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, Optical and Biological Studies on Copper(II) Complexes with 2-benzothiazolyl Hydrazones. II

Abstract: Three Cu(II) complex compounds with 4-methoxybenzaldehyde-2-benzothiazolyl hydrazone (HL) have been prepared and characterized by elemental and thermogravimetrical analysis, infrared, electronic and EPR spectra. The complex compounds have various composition and stereochemistry, depending on the reaction conditions and the metal salt used. The ligand acts as neutral bidentate NN donor in the complexes [Cu(HL) 2 (H 2 O) 2 ] . Cl 2 and [Cu(HL) 2 (H 2 O)Br] . Br and monobasic bidentate donor in the complex [Cu 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The purpose was to determine the form of coordination of these ligands and their influence on biological activity. The authors reported different copper complexes with bidentate and tridentate ligands as in Btz-16, Btz-22-Btz-24 [138], Btz-17a, Btz-17b, Btz-20 [139], and even using mixed ligands as in Btz-18, Btz-19, Btz-25 [140]. The complexes presented different distorted geometries; for example, Btz- 16 The authors reported different copper complexes with bidentate and tridentate ligands as in Btz-16, Btz-22-Btz-24 [138], Btz-17a, Btz-17b, Btz-20 [139], and even using mixed ligands as in Btz-18, Btz-19, Btz-25 [140].…”
Section: Copper Complexes With Bidentate Benzothiazole Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose was to determine the form of coordination of these ligands and their influence on biological activity. The authors reported different copper complexes with bidentate and tridentate ligands as in Btz-16, Btz-22-Btz-24 [138], Btz-17a, Btz-17b, Btz-20 [139], and even using mixed ligands as in Btz-18, Btz-19, Btz-25 [140]. The complexes presented different distorted geometries; for example, Btz- 16 The authors reported different copper complexes with bidentate and tridentate ligands as in Btz-16, Btz-22-Btz-24 [138], Btz-17a, Btz-17b, Btz-20 [139], and even using mixed ligands as in Btz-18, Btz-19, Btz-25 [140].…”
Section: Copper Complexes With Bidentate Benzothiazole Ligandsmentioning
confidence: 99%
“…The authors reported different copper complexes with bidentate and tridentate ligands as in Btz-16, Btz-22-Btz-24 [138], Btz-17a, Btz-17b, Btz-20 [139], and even using mixed ligands as in Btz-18, Btz-19, Btz-25 [140]. The complexes presented different distorted geometries; for example, Btz- 16 The authors reported different copper complexes with bidentate and tridentate ligands as in Btz-16, Btz-22-Btz-24 [138], Btz-17a, Btz-17b, Btz-20 [139], and even using mixed ligands as in Btz-18, Btz-19, Btz-25 [140]. The complexes presented different distorted geometries; for example, Btz The authors mention that it is possibly due to the more rapid diffusion of these metal complexes through the cell membrane.…”
Section: Copper Complexes With Bidentate Benzothiazole Ligandsmentioning
confidence: 99%
“…This enhanced activity of metal chelates is due to increased lipophilic nature of the metal ions in complexes. As comparatively with simple hydrazones, the benzothiazole hydrazones with metal complexes show an increasing of biological activity [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%